Force and focal adhesion assembly: a close relationship studied using elastic micropatterned substrates - Balaban, Nathalie Q.; Schwarz, Ulrich S. (Nature cell biology, 2001)
Force and focal adhesion assembly: a close relationship studied using elastic micropatterned substrates